Youth Empowerment Through Digital Marketing Training to Enhance Agricultural Product Sales in Nimbokrang Village, Jayapura Regency - Syamsidar Sinaga; Anita Rusianti; RevaniaYaiki Tenouye (AIBPM Publisher, 2025)
This community service (PkM) program was designed to empower youth in Nimbokrang Village, Jayapura Regency, through digital marketing training aimed at enhancing the sales of agricultural products. Despite the village’s rich potential in plantation commodities such as corn, chili, and tropical fruits, local farmers and youth traditionally relied on middlemen, leading to low profit margins. The program addressed these challenges by introducing participants to digital marketing strategies, with a focus on the effective use of social media platforms including Facebook, Instagram, and TikTok. Training methods combined lectures, simulations, hands-on practice, and mentoring to equip 32 participants with practical skills in creating engaging content, managing online transactions, and interacting with customers. Results indicated a significant improvement in participants’ understanding of digital marketing fundamentals, as well as their ability to produce and publish promotional content independently. The training fostered enthusiasm, creativity, and confidence among the youth, enabling them to expand market reach and reduce dependency on conventional marketing methods. Ultimately, this program not only supported local farmers in achieving more competitive prices but also encouraged the development of sustainable, digital-based business opportunities, contributing to broader economic growth in the community